Pengaruh Terapi Musik Klasik terhadap Tingkat Kecemasan Pada Ibu Hamil Primigravida Trimester III - Suharnah, Hijrianti; Jama, Fatma; S, Suhermi (Pusat Kajian dan Pengelola Jurnal Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia, 2021)
Primigravida pregnancy is a condition that causes physical and psychological changes. One of the psychological aspects that affect pregnancy and can cause anxiety. This study aims to determine the effect of classical music therapy on anxiety levels in third trimester primigravida pregnant women at UPTD Puskesmas Turikale Kab. Maros. The research design used was a quasi experiment. The research design used was